Practical training report: Kota Samarahan Municipal Council (MPKS) / Yusra Syazwani Muas - Muas, Yusra Syazwani (Universiti Teknologi MARA, Sarawak, 2017)
Kota Samarahan Municipal Council (MPKS) are located at Kota Samarahan which is 30 km from Kuching city. Kota Samarahan Municipal Council (MPKS) was gazetted on 27 December 1984 and implementing powers to governing their regions starting at 1st January 1985. The regions which control under Kota Samarahan Municipal Council (MPKS) include the small area such as Asajaya and Sadong Jaya. The MPKS is led by Mayor with allocation from the local Authority ordinance.